Synergetic role of nanoparticles and micro-scale short carbon fibers on the mechanical profiles of epoxy resin (eXPRESS Polymer Letters)
It was demonstrated in our previous work that the combined carbon nanofibers (CNFs) and microsized short carbon fibers (SCFs) in epoxy (EP) leads to significant improvements in the mechanical properties of the matrix. In this work, the effect of nano-SiO2 particles, having an extremely different aspect ratio from CNFs, on the tensile property and fracture toughness of SCFs-filled EP was studied. It was revealed that the combined use of SCFs and silica nanoparticles exerts a synergetic effect on the mechanical and fracture properties of EP. Application of SCFs and the nanoparticles is an effective way to greatly enhance the modulus, strength and fracture toughness of the EP simultaneously. The synergetic role of the multiscale fillers was explained by prominent changes in the stress state near the microsized fillers and the plastic zone ahead of the crack tip. The synergetic role of multiscale fillers is expected to open up new opportunities to formulate highperformance EP composites.